Mandibular reconstruction following oral tumor resection - Shirota, Tatsuo (Journal of The Showa University Society, 2024)
Restoration of mandibular continuity is necessary for mandibular defects after resection of oral tumors to maintain esthetics and functionality. Reconstructive plates, free bone grafts, and vascularized free bone grafts are used to restore the continuity of mandibular bone defects. Recently, customized mandibular reconstruction has been performed using computed tomography to determine the osteotomy site. This involves the use of a reconstructive plate with vascularized free bone grafts or particulate cancellous bone and marrow （PCBM） along with custom-made titanium mesh tray. This article describes mandible reconstruction using a free fibula osteocutaneous flap with microvascular anastomosis and a custom-made titanium mesh tray with PCBM harvested from the iliac crest.